Two- and three-dimensional wide-field weak lensing mass maps from the Hyper Suprime-Cam Subaru Strategic Program S16A data. (29th August 2017) - Oguri, Masamune; Miyazaki, Satoshi; Hikage, Chiaki; Mandelbaum, Rachel; Utsumi, Yousuke; Miyatake, Hironao; Takada, Masahiro; Armstrong, Robert; Bosch, James; Komiyama, Yutaka; Leauthaud, Alexie; More, Surhud; et al.
Abstract: We present wide-field (167 deg 2 ) weak lensing mass maps from the Hyper Supreme-Cam Subaru Strategic Program (HSC-SSP). We compare these weak lensing based dark matter maps with maps of the distribution of the stellar mass associated with luminous red galaxies. We find a strong correlation between these two maps with a correlation coefficient of ρ = 0.54 ± 0.03 (for a smoothing size of 8΄). This correlation is detected even with a smaller smoothing scale of 2΄ (ρ = 0.34 ± 0.01). This detection is made uniquely possible because of the high source density of the HSC-SSP weak lensing survey ($\bar{n}\sim 25\:$ arcmin −2 ). We also present a variety of tests to demonstrate that our maps are not significantly affected by systematic effects. By using the photometric redshift information associated with source galaxies, we reconstruct a three-dimensional mass map. This three-dimensional mass map is also found to correlate with the three-dimensional galaxy mass map. Cross-correlation tests presented in this paper demonstrate that the HSC-SSP weak lensing mass maps are ready for further science analyses.